Fluctuating Asymmetry as Risk Marker for Stress and Structural Defects in a Toxicologic Experiment. (26th August 2013) - Breno, Matteo; Bots, Jessica; De, Luc; Van, Stefan
<x xml:space="preserve">Abstract</x> Fluctuating asymmetry (the directionally random asymmetry of bilateral structures, FA) is commonly used as a measure of developmental instability, and may increase with stress. As several studies reported a relation between FA and developmental abnormalities, we investigate whether FA could be an additional perhaps more sensitive marker of developmental toxicity. The aim of this work is analyzing patterns of FA in multiple traits in a large dataset of rabbit fetuses, which were prenatally exposed to a toxic compound and sacrificed just before natural delivery. Gravid females were exposed to three doses of this compound, inducing abnormalities in the fetuses at the high dose only. The average FA, however, was already higher than control in rabbit fetuses of the low‐dose group but did not further increase with higher concentrations. Moreover, the increase in FA differed between traits, with the hindlimbs showing the strongest response. In addition, we did not find any association between FA and the presence of fetal abnormalities at the individual level. Although these results suggest that FA may act as "an early warning system, " we did not find a dose–response relationship with increasing stress and effects were trait‐specific. Further testing is needed before FA may be considered as a sensitive marker in developmental toxicity studies.